SPARBER PG # (Tufts Archival Research Center, 2007)
Confidential; Pages Out of Order; Summaries of various issues affecting the tobacco industry. Includes excise taxes, public smoking, advertising restrictions and coalitions. Lists the activities from the first quarter with their expected results as well as the negative occurrences of that first quarter.